STRATEGI MARKETING MIX DALAM MENINGKATKAN PENJUALAN PRODUK PADA PT ASURANSI RAMAYANA, Tbk CABANG SERANG BANTEN - Amaliya; Hasryningsih Asfar, Andy; Aziz, Abdul; Mahendra, Yoga (PEKA, 2024)
In the face of intense competition in the insurance industry, PT. Asuransi Ramayana Tbk Cabang Serang needs to implement effective marketing strategies to attract public interest and retain existing customers. This study aims to analyze marketing strategies using the 7P marketing mix approach, which includes product, price, place, promotion, people, physical evidence, and process, to enhance sales. The method used is field research with a descriptive qualitative approach and SWOT analysis. The data obtained are analyzed descriptively and through the SWOT method. The results show that PT. Asuransi Ramayana Tbk is positioned in quadrant 1, indicating strengths and opportunities from the internal perspective, such as the potential for market share development. Therefore, an aggressive strategy utilizing technology to pursue long-term opportunities is appropriate. In conclusion, the marketing strategy through the 7P marketing mix at PT. Asuransi Ramayana Tbk Cabang Serang has shown positive results in product and price aspects, but improvements are still needed in distribution channels and promotion. Furthermore, while the aspects of people, process, and physical evidence are fairly good, there are still deficiencies that need to be addressed to enhance competitiveness in an increasingly tight market